A case report of tuberculous constrictive pericarditis necessitating total pericardiectomy. Issue 9 (27th September 2021) - Yousif, Nooraldaem; Alnuwakhtha, Abdulla; Darwish, Abdulla; Arekat, Zaid; Abdulrahman, Seham
Abstract: Background: Constrictive pericarditis (CP) is one of the most serious sequelae of tuberculous pericarditis, which is characterized by heart constriction secondary to intense pericardial inflammation and thickening. Several invasive and non-invasive diagnostic modalities are crucial to address the challenges of confirming the diagnosis of CP and to expedite timely intervention. Case summary: This study reports the case of a Bahraini male with tuberculous lymphadenitis diagnosed with CP as a result of various evaluations. The patient underwent urgent total pericardiectomy and showed remarkable recovery with complete resolution of heart failure symptoms. Discussion: This case demonstrates the paramount importance of early diagnosis and treatment for patients with CP. In this unique case, the acoustic windows on echocardiography were suboptimal because of pericardial thickening. Further, computed tomography did not show significant calcification of the thickened pericardium. A novel approach of assessing haemodynamics through the right antecubital vein and right radial artery facilitated the accurate diagnosis of CP with confidence. Thereafter, successful pericardiectomy revealed a markedly thickened and stiff pericardium with many abscesses and dense adhesions encasing the heart, and pericardial biopsy showed large caseating granulomas. This case exemplifies the difficulty in diagnosing CP and the favourable outcomes achieved with well-timed surgical intervention.